A randomized, double‐blind, placebo‐controlled trial to evaluate the efficacy, safety, and tolerability of long‐term treatment with prucalopride. Issue 6 (25th March 2015) - Piessevaux, H.; Corazziari, E.; Rey, E.; Simren, M.; Wiechowska‐Kozlowska, A.; Kerstens, R.; Cools, M.; Barrett, K.; Levine, A.
Abstract Background Randomized trials have confirmed the efficacy of prucalopride for the treatment of chronic constipation up to 12 weeks. This study aimed to assess the efficacy of prucalopride over a 24‐week period (ClinicalTrials.gov: NCT01424228). Methods Adults with chronic constipation and ≤2 spontaneous complete bowel movements (SCBMs)/week were randomized to receive prucalopride 2 mg or placebo daily for 24 weeks. The primary endpoint was the proportion of patients achieving a mean of ≥3 SCBMs/week over the treatment period, assessed using daily e‐diaries. Secondary outcomes and safety parameters were assessed throughout the study. Key Results Overall, 361 patients were randomized and received prucalopride or placebo. Baseline characteristics were similar in the prucalopride (N = 181) and placebo (N = 180) groups. Mean age was 48.9 years (standard deviation, 16.0) and most patients were women. The proportion of participants achieving the primary endpoint was not statistically different between the prucalopride and placebo groups (25.1% vs 20.7%; p = 0.367). There was also no statistically significant difference between groups over the first 12‐week period (prucalopride, 25.1%; placebo, 20.1%; p = 0.341). There were no statistically significant differences between groups for most secondary endpoints. No new safety concerns were identified. Conclusions & Inferences This trial did not show statistically significant improvements in primary or secondary outcomes with prucalopride compared with placebo over 24 or 12 weeks. This is in contrast to the results of four previous 12‐week trials, which demonstrated prucalopride to be significantly more effective than placebo. An extensive evaluation did not provide an explanation for the null efficacy results of this study.